Heterogeneity, politics of ethnicity, and multiculturalism; What is a viable framework for Indonesia? - Lan, Thung Ju (UI Scholars Hub, 2011)
Indonesia is a plural society that consists of several hundred ethnic and sub-ethnic groups. One of its generic characteristics is heterogeneity. In the last ten years after the implementation of regional autonomy, we have witnessed the emergence of strong ethnic and religiously flavoured local identity politics in various places in Indonesia that created open and vicious conflicts. This periodical violence exploded especially during the election of district and provincial heads. The intimate relation multiculturalism, with the actual political praxis of everyday life as an alternative to the existing paradigm of the